Critical Appraisal of International Guidelines for the Management of Diabetic Neuropathy: Is There Global Agreement in the Internet Era? - Mingfang Sun; Min Zhang; Jing Shen; Juping Yan; Bo Zhou (International Journal of Endocrinology)
Purpose. The management of diabetic neuropathy (DN) can be challenging. There exist many guidelines for DN management, but the quality of these guidelines has not been systematically evaluated or compared. The objective of our study was to assess the quality of these guidelines as a step toward their future optimization, the development of international guidelines, and, ultimately, the improvement of the care process. Methods. Relevant data were selected to identify international guidelines. The Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool was used to evaluate the quality of the selected guidelines. In addition, the reviewers summarized and compared all of the recommendations from the included guidelines for DN’s management. Results. Thirteen guidelines were included after the selection process. According to AGREE II, few guidelines scored well for all three aspects of DN management. Detailed comparisons revealed that these guidelines provide inconsistent recommendations, making it difficult for diabetes clinicians to choose appropriate guideline. Conclusions. The quality of most guidelines for the management of DN should be improved. Further studies should concentrate on developing internationally accepted and evidence-based guidelines that could be used for clinical decision making to improve patient care.